From Young to Old: Mimicking Neuronal Aging in Directly Converted Neurons from Young Donors - Varghese, N; Grimm, A; Cader, MZ; Eckert, A (MDPI, 2024)
A substantial challenge in human brain aging is to find a suitable model to mimic neuronal aging in vitro as accurately as possible. Using directly converted neurons (iNs) from human fibroblasts is considered a promising tool in human aging since it retains the aging-associated mitochondrial donor signature. Still, using iNs from aged donors can pose certain restrictions due to their lower reprogramming and conversion efficacy than those from younger individuals. To overcome these limitations, our study aimed to establish an in vitro neuronal aging model mirroring features of in vivo aging by acute exposure on young iNs to either human stress hormone cortisol or the mitochondrial stressor rotenone, considering stress as a trigger of in vivo aging. The impact of rotenone was evident in mitochondrial bioenergetic properties by showing aging-associated deficits in mitochondrial respiration, cellular ATP, and MMP and a rise in glycolysis, mitochondrial superoxide, and mitochondrial ROS; meanwhile, cortisol only partially induced an aging-associated mitochondrial dysfunction. To replicate the in vivo aging-associated mitochondrial dysfunctions, using rotenone, a mitochondrial complex I inhibitor, proved to be superior to the cortisol model. This work is the first to use stress on young iNs to recreate aging-related mitochondrial impairments.